The Dynamics of Corporate Governance, Earnings Management, and Market Risk in Enhancing Corporate Value: Evidence from the Indonesian Sharia Capital Market - Subqi, Tajus (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study aims to examine and analyse the factors influencing the value of companies in the Indonesian Sharia capital market, including corporate governance, earnings management, market risk, investment decisions, and dividend policy. Using secondary data from the Annual Report, Factbook IDX, and ICMD, and descriptive analysis using SPSS 28 and PLS-SEM, the study focuses on 71 sample companies from the Indonesian Sharia Stock Index (ISSI) during 2017-2022. The findings indicate that dividend policy and investment decisions significantly influence the mediating role of corporate governance on firm value, with a negative impact on firm value when corporate governance is high. Dividend policy does not significantly moderate the impact of earnings management and market risk on firm value, and investment decisions do not moderate the impact of earnings management. However, investment decisions significantly mediate the impact of market risk on firm value, with risk-orientated investors increasing firm value through short-term transactions, providing a new perspective on the relationship between investment decisions and firm value.